PENGGUNAAN PENDEKATAN SAINTIFIK MELALUI MODEL PEMBELAJARAN VIDEO SESSION, POSTER SESSION DAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN PAI - Rohmah, Liatul (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
The objective of the study is to describe the usage of scientificapproach through learning model of video session, poster session andinformation technology based in learning of Islamic Education atSMPN 3 Tulungagung and SMPN 3 Peterongan Jombang. Thedesign use in the study is qualitative approach. Collecting data isconducted by interviewing techniques, observation anddocumentation. Data analysis applies data analysis of personal caseand crossing case. The result of the study shows that using scientificapproach through learning model of video session, using postersession, or based on information technology produces as follows: inthe beginning of learning, every teacher starts it by greeting, praying,checking studentsâ attendance and explaining activities will be doneincluding material, method, evaluation and so forth. In the whileactivities embraces the process of (1) observing, (2) formulatingquestions, (3) collecting data (4) associating, and (5)communicating. Final activities are conducting remidi and assigninghomework, praying and greeting.Keyword: Learning Model, Video, Scientific Approach, Video,Internet.